PERAN BADAN PENGAWAS PEMILIHAN UMUM DALAM MENCEGAH PELANGGARAN POLITIK DI KABUPATEN OGAN KOMERING ULU - Dina Julia; Kelin Ersalia; Tara Pebiola; Andika Firandes; Eva Susanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze in depth the role of the Election Supervisory Agency (Badan Pengawas Pemilihan Umum / Bawaslu) in preventing political violations in Ogan Komering Ulu Regency. The main problem addressed in this research is the persistence of various forms of political violations, such as vote buying, black campaigns, and administrative violations, which have the potential to undermine the quality of democracy at the local level. This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, documentation, and literature review. Data analysis was conducted through stages of data reduction, data presentation, and conclusion drawing, using triangulation techniques to ensure data validity. The results of the study indicate that the Election Supervisory Agency (Bawaslu) of Ogan Komering Ulu Regency has performed its role quite optimally through the supervision of election stages, political socialization, vulnerability mapping, inter-institutional coordination, and enforcement of violations. However, the effectiveness still faces structural and cultural constraints, such as limited human resources, the wide supervisory area, and low political awareness among the community. Therefore, strengthening institutional capacity and increasing public participation are necessary to support the realization of high-quality elections.